2017
DOI: 10.3389/fphar.2017.00804
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of NAC1 Expression Induces Cancer Cells Oxidative Stress in Hypoxia and Potentiates the Therapeutic Activity of Elesclomol

Abstract: In order to survive under conditions of low oxygen, cancer cells can undergo a metabolic switch to glycolysis and suppress mitochondrial respiration in order to reduce oxygen consumption and prevent excessive amounts of reactive oxygen species (ROS) production. Nucleus accumbens-1 (NAC1), a nuclear protein of the BTB/POZ gene family, has pivotal roles in cancer development. Here, we identified that NAC1-PDK3 axis as necessary for suppression of mitochondrial function, oxygen consumption, and more harmful ROS g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 35 publications
(42 reference statements)
0
17
0
Order By: Relevance
“…Elesclomol shows potent antitumor activity against a broad spectrum of cancers; this activity is exerted via increasing ROS and oxidative stress to levels that are lethal to cells [21]. Flow cytometry showed that the average fluorescence intensity of the elesclomoltreated cells increased as the drug concentration increased, as compared with the negative-control cells (Fig.…”
Section: Elesclomol Promotes Myofibroblast Apoptosis By Increasing Oxidative Stressmentioning
confidence: 93%
See 1 more Smart Citation
“…Elesclomol shows potent antitumor activity against a broad spectrum of cancers; this activity is exerted via increasing ROS and oxidative stress to levels that are lethal to cells [21]. Flow cytometry showed that the average fluorescence intensity of the elesclomoltreated cells increased as the drug concentration increased, as compared with the negative-control cells (Fig.…”
Section: Elesclomol Promotes Myofibroblast Apoptosis By Increasing Oxidative Stressmentioning
confidence: 93%
“…Elesclomol has received both fast track and orphan drug status from the U.S. Food and Drug Administration for the treatment of metastatic melanoma [17,18] and it is also being used in tumors such as non-small cell lung cancer, breast cancer and sarcoma [19,20]. Recently, elesclomol was shown to induce ROS production in tumor cells in vitro, leading to increased oxidative stress and apoptosis [21,22]. Considering its proapoptotic effects, we speculated that elesclomol may serve as a novel treatment for HS.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that hypoxia-inducible factor (HIF)-1α regulates the expression of pyruvate dehydrogenase kinase 3 (PDK3) and further induces chemotherapy resistance under hypoxic conditions (43,46). Nucleus accumbens-1 mediates the inhibition of mitochondrial function via HIF-1α-mediated PDK3 overexpression, the inhibition of pyruvate dehydrogenase function and the repression of mitochondrial respiration (47). This process can protect cancer cells from apoptosis under hypoxic conditions (47).…”
Section: Pyruvate Kinase (Pkm2)mentioning
confidence: 99%
“…Nucleus accumbens-1 mediates the inhibition of mitochondrial function via HIF-1α-mediated PDK3 overexpression, the inhibition of pyruvate dehydrogenase function and the repression of mitochondrial respiration (47). This process can protect cancer cells from apoptosis under hypoxic conditions (47). Upregulation of PDK4 increases resistance to chemotherapy in hepatocytes and colon cancer cells (48).…”
Section: Pyruvate Kinase (Pkm2)mentioning
confidence: 99%
“…In doing so, cancer cells may lose their ability to thrive under environments containing a higher concentration of ROS compared with normal healthy cells. One example is the silencing of nucleus-accumbens-1 (NAC1), which has been shown to facilitate oxidative stress resistance, sensitizing cancer cells to oxidative stress generating chemotherapeutics [121]. Pyrroline-5-carboxylate reductase 1 and 2 (PYCR1, PYCR2) downregulation or silencing could potentially sensitize cancer cells to ROS by inhibiting stress-response protein ribonucleotide reductase small subunit B (RRM2B), a protein implicated in protection from oxidative stress [122].…”
Section: Strategies To Target Mitochondriamentioning
confidence: 99%